Mapping and change detection of mangrove forest in Sakhartar estuary of Ratnagiri district, Maharashtra - Nakhawa, Ajay D; Markad, Sandip S; Vichare, Priyanka S; Shirdhankar, Mangesh M (International Multidisciplinary Research Journal, 2012)
The mangroves along the estuaries of Ratnagiri, India have remained largely investigated. The present study described the Mangrove of the Sakhartar estuary located in Ratnagiri district, Maharashtra. The mangrove maps of estuary was prepared using the unsupervised classification of principal components technique of Landsat-TM, Landsat-ETM, ASTER, IRS-P6 (LISS III) satellite data 1989, 1999, 2004 and 2009 respectively. The mangrove coverage of Sakhartar estuary in 2009 was about 297.36 ha, while mangrove coverage in 1989, 1999 and 2004 were 109.13, 188.62 and 203.45 hectare respectively. Eight species of mangrove such as Sonneratia alba, Avicennia spp., Rhizophora mucronata, Acanthus ilicifolius, Ceriops tagal, Lumnitzera racemosa, Excoecaria agallocha and Aegiceras corniculatum were observed along the sakhartar estuary which makes it one of the diverse estuary in Maharashtra. The post-classification approach was adopted for changed detection study. The Sakhartar estuary showed net increase in mangrove coverage for all the time period. The overall change was characterised by the huge net increase of 188.24 ha mangrove forest, due to widening of mangrove forest on the mudflats of the estuarine.